Guidelines for vitamin K prophylaxis in newborns - Ng, Eugene (Paediatr Child Health, 2018)
Newborns are at risk for vitamin K deficiency bleeding (VKDB) caused by inadequate prenatal storage and deficiency of vitamin K in breast milk. Systematic review of evidence to date suggests that a single intramuscular (IM) injection of vitamin K at birth effectively prevents VKDB. Current scientific data suggest that single or repeated doses of oral (PO) vitamin K are less effective than IM vitamin K in preventing VKDB. The Canadian Paediatric Society and the College of Family Physicians of Canada recommend routine IM administration of a single dose vitamin K at 0.5 mg to 1.0 mg to all newborns. Administering PO vitamin K (2.0 mg at birth, repeated at 2 to 4 and 6 to 8 weeks of age), should be confined to newborns whose parents decline IM vitamin K. Health care providers should clarify with parents that newborns are at increased risk of VKDB if such a regimen is chosen. Current evidence is insufficient to recommend routine intravenous vitamin K administration to preterm infants undergoing intensive care.